Students’ Intrinsic and Extrinsic Motivation in Learning the English Language - Sidónio António Pires (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
New starts require new motivation. Students also need motivation to learn the English language. Several studies have shown that motivation is crucial in learning English and depends mostly on extrinsic motivation rather than intrinsic motivation.The purpose of the study was to describe the students’ intrinsic and extrinsic motivation in learning the English language at Instituto São João de Brito (ISJB), Kasait, Timor-Leste. The study aimed to answer the main problems: 1) What kind of motivation do the students use to learn English? 2) How motivated are the students to learn the English Language?.The researchers applied a mixed-method approach. The data were collected from 33 respondents using a questionnaire and interview. The data gained were interpreted and analyzed descriptively. The quantitative findings show that the student’s intrinsic motivation was higher than extrinsic motivation as rated with a mean of 4.22 out of 5. The extrinsic motivation was rated with a mean of 3.79, which is high. The qualitative findings revealed that the students took the English language as more than just an instrument for achieving academic goals. It was seen as an exciting language to learn.This study recognizes the importance of motivation to learn English and ultimately intrinsic motivation. It prompts future researchers to conduct similar research in various learning contexts to generate more findings